The Fog of War: Russia's War on Ukraine, European Defence Spending and Military Capabilities - Daniel Fiott (Intereconomics, 2022)
Some … may look at the depleted nature of Russia's military after its invasion of Ukraine and incorrectly surmise that defence spending increases are not that necessary after all.
Keywords: O33; F50; N44; 330